PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK LISTRIK DINAMIS DI KELAS X SEMESTER II SMA NEGERI 1 PARANGINAN T.P 2015/2016 - Siburian, Erisal; Harahap, Mukti Hamjah (Universitas Negeri Medan, 2016)
This study aims to determine the effect of cooperative learning model Numbered Heads Together (NHT) to the learning outcomes of students in the subject matter dynamic power in the second half of the class X SMA Negeri 1 Paranginan T.P 2015 / 2016. This research is quasi experimental design with two group pretest -postest. Sampling was done by class random sampling of the population of all students in grade Class X SMA N 1 Paranginan which consists of classes X-A totaling 31 people as an experimental class X and class-B amounting to 31 people as a control group. The instrument used in this study is the achievement test in the form of multiple-choice has been declared valid by the validator. Hypothesis test results using a different test (t-test) showed that student learning outcomes as a result of the influence of cooperative learning model Numbered Heads Together is better on the dynamic electrical material in the second semester of grade X SMAN 1 Paranginan T.P.2015 / 2016.